2020
DOI: 10.1186/s12888-020-02721-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-way messaging therapy for depression and anxiety: longitudinal response trajectories

Abstract: Background: Telemedicine is a strategy for overcoming barriers to access evidence-based psychotherapy. Digital modalities that operate outside session-based treatment formats, such as ongoing two-way messaging, may further address these challenges. However, no study to date has established suitability criteria for this medium. Methods: A large outpatient sample (n = 10,718) engaged in daily messaging with licensed clinicians from a telemedicine provider. Patients consisted of individuals from urban and rural s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…The lack of diversity might limit the generalizability of our results, because race and gender in particular play a role in exposure to and development of PTSD as well as treatment seeking behaviors (Roberts et al, 2011). However, the study make-up is similar to that reported elsewhere for the platform (Hull et al, 2020) and for the use of telehealth in more traditional therapy settings as well (Titov et al, 2017). Future research should address the limitations of this study by including a fully-powered randomized design, objective assessments, a more standardized comparison condition, a more diverse and larger sample, and systematic documentation of reasons for dropout.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The lack of diversity might limit the generalizability of our results, because race and gender in particular play a role in exposure to and development of PTSD as well as treatment seeking behaviors (Roberts et al, 2011). However, the study make-up is similar to that reported elsewhere for the platform (Hull et al, 2020) and for the use of telehealth in more traditional therapy settings as well (Titov et al, 2017). Future research should address the limitations of this study by including a fully-powered randomized design, objective assessments, a more standardized comparison condition, a more diverse and larger sample, and systematic documentation of reasons for dropout.…”
Section: Discussionmentioning
confidence: 77%
“…TAU was conducted with clients who enrolled in Talkspace through the platform's normal onboarding and intake processes. While therapists who utilize the platform report a variety of therapeutic approaches and areas of expertise (see Hull et al, 2020 for a full description of the therapy network), those therapists who endorsed a specialty in treating PTSD and who identified CBT as one of their orientations were selected for this study. Clients who were being treated by these clinicians primarily for their PTSD-related symptoms were selected.…”
Section: Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Talkspace also allows psychotherapists to schedule live video sessions with patients within their regions of licensure. Studies have shown that Talkspace is acceptable and feasible for increasing patients’ access to care [ 6 ]. Talkspace has been used by over 2000 therapists who each serve an average of 15-20 patients at any given time (ie, throughout the United States and worldwide).…”
Section: Methodsmentioning
confidence: 99%